The Climate Action Plan of the city of Teresina, PI and the case of the Vila da Paz neighborhood: perpetuating inequalities in vulnerable urban territories - Mendes, Élgen Soares; Toledo , Renata Ferraz de (Technical and Scientific Journal Green Cities, 2025)
Objective – to analyze the Vila da Paz Urbanization Project from the perspective of creating adaptive capacities and climate resilience.Methodology – qualitative case study, supported by bibliographical and documentary research and field surveys.Originality/Relevance – bring science, politics, and society closer together, and raise awareness among public policymakers about the urgency of taking action to to address the possibility of these policies promoting climate injustices.Results – The Vila da Paz Urbanization Project did not promote the creation of adaptive capacities and climate resilience; on the contrary, it created new vulnerabilities and increased some of the existing ones.Theoretical/Methodological Contributions – highlights the importance of studies that critically analyze public policies and their implications in vulnerable urban areas. Social and Environmental Contributions – highlights the importance of social participation and intersectionality studies in the development of public climate policies.
Keywords: Climate change; Public policies; Climate injustice